Search Strategies Tutorial - Bednar, Magen E.; Boulden, Kristal; Curry, Claire M.; Schilling, Amanda; Tweedy, Brent N.; Antell, Karen; Albin, Joey (My University, 2020)
Search Strategies Tutorial for the University of Oklahoma Libraries
Keywords: Bibliographic Instruction; Consultations; Curriculum; Exercises; Information Literacy; Instruction Sessions; Libraries; Library; Library Instruction; Library Resources; Presentations; Resources; Slides; Training; Worksheets; Workshops